COVID-19 pandemic: lessons learned from more than a century of pandemics and current vaccine development for pandemic control - Buchy, Philippe; Buisson, Yves; Cintra, Otavio; Dwyer, Dominic E.; Nissen, Michael; Ortiz de Lejarazu, Raul; Petersen, Eskild (International journal of infectious diseases, 2021)
•Previous pandemic experience informs COVID-19 vaccine development•Vaccines using different platforms have been developed at unprecedented speed•In a new emergency, vaccine backbones might be used swiftly with a novel antigen•Active surveillance for emerging variants or new pathogens is essential•Production of sufficient vaccine for all countries and ages remains a challenge Pandemic dynamics and health care responses are markedly different during the COVID-19 pandemic than in earlier outbreaks. Compared with established infectious disease such as influenza, we currently know relatively little about the origin, reservoir, cross-species transmission and evolution of SARS-CoV-2. Health care services, drug availability, laboratory testing, research capacity and global governance are more advanced than during 20th century pandemics, although COVID-19 has highlighted significant gaps. The risk of zoonotic transmission and an associated new pandemic is rising substantially. COVID-19 vaccine development has been done at unprecedented speed, with the usual sequential steps done in parallel. The pandemic has illustrated the feasibility of this approach and the benefits of a globally coordinated response and infrastructure. Some of the COVID-19 vaccines recently developed or currently in development might offer flexibility or sufficiently broad protection to swiftly respond to antigenic drift or emergence of new coronaviruses. Yet many challenges remain, including the large-scale production of sufficient quantity of vaccines, delivery of vaccines to all countries and ensuring vaccination of relevant age groups. This wide vaccine technology approach will be best employed in tandem with active surveillance for emerging variants or new pathogens using antigen mapping, metagenomics and next generation sequencing.